Satellite Gravity Gradiometry: Secular Gravity Field Change over Polar Regions - Moore, Philip; King, Matt A. (Journal of Geodynamics, 2010)
International audience The ESA Gravity and steady state Ocean and Circulation Explorer, GOCE, mission will utilise the principle of satellite gravity gradiometry to measure the long to medium wavelengths in the static gravity field. Previous studies have demonstrated the low sensitivity of GOCE to ocean tides and to temporal gravity field variations at the seasonal scale. In this study we investigate the sensitivity of satellite gradiometry missions such as GOCE to secular signals due to ice-mass change observed in Greenland and Antarctica. We show that unaccounted ice mass change signal is likely to increase GOCE-related noise but that the expected present-day polar ice mass change is below the GOCE sensitivity for an 18 month mission. Furthermore, 2-3 orders of magnitude improvement in the gradiometry in future gradiometer missions is necessary to detect ice mass change with sufficient accuracy at the spatial resolution of interest.